"It's Just Not the Culture": A Qualitative Study Exploring Residents' Perceptions of the Impact of Institutional Culture on Feedback. Issue 2 (3rd April 2017) - Ramani, Subha; Post, Sarah E.; Könings, Karen; Mann, Karen; Katz, Joel T.; van der Vleuten, Cees
ABSTRACT: Phenomenon : Competency-based medical education requires ongoing performance-based feedback for professional growth. In several studies, medical trainees report that the quality of faculty feedback is inadequate. Sociocultural barriers to feedback exchanges are further amplified in graduate and postgraduate medical education settings, where trainees serve as frontline providers of patient care. Factors that affect institutional feedback culture, enhance feedback seeking, acceptance, and bidirectional feedback warrant further exploration in these settings. Approach: Using a constructivist grounded theory approach, we sought to examine residents' perspectives on institutional factors that affect the quality of feedback, factors that influence receptivity to feedback, and quality and impact of faculty feedback. Four focus group discussions were conducted, with two investigators present at each. One facilitated the discussion, and the other observed the interactions and took field notes. We audiotaped and transcribed the discussions, and performed a thematic analysis. Measures to ensure rigor included thick descriptions, independent coding by two investigators, and attention to reflexivity. Findings : We identified five key themes, dominated by resident perceptions regarding the influence of institutional feedback culture. The theme labels are taken from direct participant quotes: (a) the cultural norm lacks clear expectations and messages around feedback, (b) the prevailing culture of niceness does not facilitate honest feedback, (c) bidirectional feedback is not part of the culture, (d) faculty–resident relationships impact credibility and receptivity to feedback, and (e) there is a need to establish a culture of longitudinal professional growth. Insights: Institutional culture could play a key role in influencing the quality, credibility, and acceptability of feedback. A polite culture promotes a positive learning environment but can be a barrier to honest feedback. Feedback initiatives focusing solely on techniques of feedback giving may not enhance meaningful feedback. Further research on factors that promote feedback seeking, receptivity to constructive feedback, and bidirectional feedback would provide valuable insights.